Analisis Faktor-faktor yang Mempengaruhi Persepsi Etis Akuntan Masa Depan dengan Love of Money sebagai Variabel Intervening - Rizki Listyono Putro; Eva Wany; Sarah Yuliarini (Politeknik Keuangan Negara STAN, 2020)
The attitude of accountant's tendency to become wealthy was initiated at the beginning of determining them as professions. Whether from the beginning they have the perception of being rich quickly from the wealth of others, so that from the beginning to be embedded the intention will justify all means to redefine the desire. They are prospective accountants who are supposed to be equipped with a basic knowledge of ethics. This thesis aims to empirically evaluate factors that influence the ethical perception of future accountants with love of money as the intervening variable, its free variable is gender, academic achievement, and locus of control. The most variable is the ethical perception of future accountants. Selection of research samples using purposive samples, and a sampling of 90 respondents. Data analysis techniques using SEM (Structural Equation Modeling) with SmartPLS Program version 3.0. There are three conclusions of the research analysis results namely: indirect influence of the gender variables against ethical perception through love of money is an uninfluential and insignificant, indirect influence of variable academic achievement to the ethical perception of future accountants through love of money has no effect and insignificant, and indirect influence of the variable locus of control to the ethical perception of future accountants through the love of money.